Keyakinan sebagai Faktor Penting dalam Kepatuhan Pengobatan TB pada Anak - Devi Trianingsih; Dessie Wanda; Fajar Tri Waluyanti (JURNAL KEPERAWATAN RAFLESIA, 2019)
Children are one of the most vulnerable populations to the spread of tuberculosis (TB) ger, however, unfortunately the success of TB treatment in DKI Jakarta is still quite low. This study aimed to determine the factors that most influence TB child treatment adherence. The method used was descriptive analysis with cross sectional approach. The sample was determined using techniques Consecutive Sampling: Non Probability Sampling which numbered 168 people. This study illustrated that belief variable was the most influencing factors of TB treatment adherence in children (p value 0,001; α=0.05; OR 8,02 after controlled by long-term treatment of TB, PMO, cognitive developments stages, coping behaviour, memory, treatment regimens, communication with health care providers, social support and access to health facilities. This study expected to be source of knowledge for nurses to provide client’s belief and improve adherence to TB treatment in children.